2023
DOI: 10.1021/acsomega.3c01019
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz Spectroscopy and DFT Analysis of Phonon Dynamics of the Layered Van der Waals Semiconductor Nb3X8 (X = Cl, I)

Abstract: We have conducted a terahertz spectroscopic study and a density functional theory analysis of the phonon dynamics of the layered van der Waals semiconductors Nb3Cl8 and Nb3I8. Several infrared-active phonon modes were observed in the terahertz region, and their frequencies were found to be in excellent agreement with our first-principles lattice dynamics calculations. For Nb3Cl8, the observed phonon spectra are consistent with a structural transition at 90 K from the high-temperature P3̅m1 phase to the low-tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…The magnetic susceptibility of the material with respect to temperature in figure 1(d) shows hysteresis between the cooling and heating transitions, with the critical cooling temperature found to be at 90 K and the critical heating temperature found to be at 103 K, both corresponding to the transition from a paramagnetic state at room temperature to a nonmagnetic singlet state [5,6] at low temperatures. This magnetic transition has been linked to the structural phase transition which Nb 3 Cl 8 undergoes at low-temperatures in the literature, and therefore the presence of this magnetic transition in our data is the evidence that the structural transition has occurred [4][5][6][7].…”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations
“…The magnetic susceptibility of the material with respect to temperature in figure 1(d) shows hysteresis between the cooling and heating transitions, with the critical cooling temperature found to be at 90 K and the critical heating temperature found to be at 103 K, both corresponding to the transition from a paramagnetic state at room temperature to a nonmagnetic singlet state [5,6] at low temperatures. This magnetic transition has been linked to the structural phase transition which Nb 3 Cl 8 undergoes at low-temperatures in the literature, and therefore the presence of this magnetic transition in our data is the evidence that the structural transition has occurred [4][5][6][7].…”
Section: Resultssupporting
confidence: 73%
“…In this case, there is a significant change in the type of Raman active phonons expected for the low-temperature phase (A g and B g ) as well as the Raman tensors governing the polarization selection rules [37][38][39]. However, other groups have reported that the low-temperature phase corresponds to the R 3m space group instead [5,7]. Since crystals with P 3m1 and R 3m symmetries share the same point group (D 3d ) and hence the same Raman tensors for the A g and E g modes, there would be no difference in the polarization-dependence of these modes.…”
Section: Room and Low-temperature Polarized Raman Analysismentioning
confidence: 99%
See 2 more Smart Citations